Modelling of Mechatronic System with Linear Induction Motors - Rinkevičienė, R.; Lisauskas, S. (Elektronika ir Elektrotechnika, 2003)
Mechatronic systems with linear induction motors are applied for short time duty type. During this operation speed of the secondaryelement and currents f inductor do not reach steady state values. To investigate dynamics of linear induction drive it was carried out twotypes of dynamic models: one in synchronous reference frame, other in fixed reference frame. Elaborated algorithm and program withcommand window facilitates investigation of dynamic characteristics when are known parameters of equivalent circuit. Carried outmodel of linear electric drive gives the same results . Ill. 8, bibl. 17 (in Lithuanian, summaries in Lithuanian, English and Russian).